Сучасні аспекти управління виробничим потенціалом промислових підприємств - Петрович, Й. М.; Прокопишин-Рашкевич, Л. М.; Petrovych, Y.; Prokopyshyn-Rashkevych, L. (Видавництво Львівської політехніки, 2020)
Висвітлено теоретичні аспекти виробничого потенціалу промислового підприємства. Зокрема з’ясовано відповідні проблемні питання, які стосуються змістового наповнення поняття “виробничий потенціал промислового підприємства (ВППП)”. На основі вивчення і узагальнення досліджень, які проведені науковцями протягом останніх років, зроблено спробу подати авторське визначення виробничого потенціалу промисловго підприємства. Увага акцентується на тому, що особливості управління виробничим потенціалом повинні бути пов’язаними із новим типом інноваційних виробничих відносин в умовах прискореного науково-технічного прогресу.

The theoretical aspects of production potential of industrial enterprise are revealed in the article. The authors considered different approaches linked to the meaning of enterprise’s production potential. It was taken into account a lot of definitions given by various authors in their scientific, education research over the last 10-15 years. In accordance to the study and generalization of research carried out by scientists in recent years, it was made an attempt to present the authors’ definition of production potential. The definition is related to the theoretical and methodological approaches to understanding the enterprise’s production potential as an economic category, which reflects and characterizes a new type of industrial relations in the context of accelerated scientific and technological progress. Without doubt, scientific and technological progress has a significant impact on the development of industrial enterprises, their potential ability to successfully fulfill their economic and social functions to the changing conditions. The enterprise’s production potential has a characteristic feature linked to dynamic nature and some changes, which are provoked by the influence of some external and internal factors. They have a significant impact on the activity of industrial enterprises. Nowadays, in the conditions of rapid scientific and technological progress, all enterprises should increase their innovative activity via systematically taking care of professional competency of their staff, modernization of their material and technical base. In addition, the management of industrial enterprises faces a number of problematic tasks, which determine the development and implementation of organizational and technical measures aimed at adaptation of most enterprises and their production potential. Thus, the authors point out industrial enterprises should refocus on production organization in line with consumer demand. Such industrial products must meet certain quality standards and replace imported goods. It is concluded that industrial enterprises should organize their production on an innovative basis and develop their production potential as prerequisite for successful activity.
Modern management aspects of industrial enterprises’ production potential
Keywords: виробничий потенціал; промислове підприємство; модернізація; виробничі ресурси; production potential; industrial enterprise; modernization; production resources; L60; O; 31; 658.012.2